The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.omtn.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome-Level Study Identifies Changing Expression Profiles for Ossification of the Ligamentum Flavum of the Spine

Abstract: Ossification of the ligamentum flavum (OLF) is a common spinal disorder that causes myelopathy and radiculopathy. Non-coding RNAs (ncRNAs) are involved in numerous pathological processes; however, very few ncRNAs have been identified to be correlated with OLF. Here we compared the expression of lncRNA, mRNA, circRNA, and microRNA in OLF tissues from OLF patients and healthy volunteers through mRNA, lncRNA, and circRNA microarrays and microRNA sequencing. A total of 2,054 mRNAs, 2,567 lncRNAs, 627 circRNAs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Systemic variations between the expressions of miRNAs in four human OLF samples and four normal ligamentum flavum (LF) samples were previously identified using miRNA sequencing analysis , from which we noted that miR‐342‐3p was over‐expressed in OLF (Fig. A).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Systemic variations between the expressions of miRNAs in four human OLF samples and four normal ligamentum flavum (LF) samples were previously identified using miRNA sequencing analysis , from which we noted that miR‐342‐3p was over‐expressed in OLF (Fig. A).…”
Section: Resultsmentioning
confidence: 75%
“…A). Systemic variations between the expression of mRNAs in four human ossified LF samples and four normal LF samples were previously identified using a microarray analysis , from which we noted that ATF3 was remarkably down‐regulated in ossified LF (Fig. B) (The microarray data have been uploaded to NCBI Gene Expression Omnibus and can be adopted by GEO Series accession number ).…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, lncRNAs may also be important targets for the treatment of OLF. However, OLF-related lncRNAs are rarely reported, with the exception of the a previous study by Han et al (22).…”
Section: Introductionmentioning
confidence: 91%
“…The aim of the present study was to use the datasets uploaded by Han et al (22) to further identify novel miRNAs and crucial lncRNAs for OLF based on the miRNA-mRNA and lncRNA-miRNA-mRNA ceRNA regulatory networks. The findings may provide insight for underlying therapeutic strategies for OLF by changing the expression levels of miRNAs and lncRNAs, which could in turn regulate the target genes.…”
Section: Introductionmentioning
confidence: 99%
“…long non-coding rnas (lncrnas) are autonomously transcribed non-coding rnas, which are >200 nucleotides in length (6). lncrnas can act at the transcriptional, post-transcriptional and epigenetic levels via cis-or trans-acting pathways (7,8). Previous studies have reported the potential importance of lncrnas in maintaining the intestinal barrier and mediating inflammatory lesions (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%